Low copy repeats mediate distal chromosome 22q11.2 deletions: Sequence analysis predicts breakpoint mechanisms - Shaikh, Tamim H. (Cold Spring Harbor Laboratory Press, 2007)
Genomic disorders contribute significantly to genetic disease and, as detection methods improve, greater numbers are being defined. Paralogous low copy repeats (LCRs) mediate many of the chromosomal rearrangements that underlie these disorders, predisposing chromosomes to recombination errors. Deletions of proximal 22q11.2 comprise the most frequently occurring microdeletion syndrome, DiGeorge/Velocardiofacial syndrome (DGS/VCFS), in which most breakpoints have been localized to a 3 Mb region containing four large LCRs. Immediately distal to this region, there are another four related but smaller LCRs that have not been characterized extensively. We used paralog-specific primers and long-range PCR to clone, sequence, and examine the distal deletion breakpoints from two patients with de novo deletions mapping to these distal LCRs. Our results present definitive evidence of the direct involvement of LCRs in 22q11 deletions and map both breakpoints to the BCRL module, common to most 22q11 LCRs, suggesting a potential region for LCR-mediated rearrangement both in the distal LCRs and in the DGS interval. These are the first reported cases of distal 22q11 deletions in which breakpoints have been characterized at the nucleotide level within LCRs, confirming that distal 22q11 LCRs can and do mediate rearrangements leading to genomic disorders.